Towards exploring features of Hamiltonian renormalisation relevant for quantum gravity. (7th April 2022) - Bahr, Benjamin; Liegener, Klaus
Abstract: We consider the Hamiltonian renormalisation group (RG) flow of discretised one-dimensional physical theories. In particular, we investigate the influence the choice of different embedding maps has on the RG flow and the resulting continuum limit, and show in which sense they are, and in which sense they are not equivalent as physical theories. We are furthermore elucidating on the interplay of the RG flow and the algebras which operators satisfy, both on the discrete and the continuum. Further, we propose preferred renormalisation prescriptions for operator algebras guaranteeing to arrive at preferred algebraic relations in the continuum, if suitable extension properties are assumed. Finally, we introduce a weaker form of distributional equivalence, and show how unitarily inequivalent continuum limits, which arise due to a choice of different embedding maps, can still be weakly equivalent in that sense. We expect these results to have application in defining an RG flow in loop quantum gravity.